Migration To and From Wisconsin - Lopez, Yeri; Scholz, John Karl (My University, 2007)
Wisconsin exports more college graduates than it imports, with a net 7,000 people with bachelor's degrees leaving, the authors discover. More educated people leave Wisconsin for Chicago and Minneapolis/St. Paul than leave Illinois or Minnesota for Milwaukee.